(untitled) (Global Journal of Medical Research, 2023)
One should act on the level of the causes and not the effects Cancer does not come by coincidence it does not come out of nowhere There is usually a chain of prerequisites or conditions that can be divided into somatic mental and psychological If you limit yourself to only fighting the tumor you do not change the fact that the organism produced it for a reason Therefore it is worth going to the level of possible causes and trying to treat and eliminate them Such causes are for example toxins of chemical nature but also mental and psychological poisons such as repressed conflicts The purification of the body-mind-soul unity is the best cancer prevention therapy